2019
DOI: 10.2319/061318-443.1
|View full text |Cite
|
Sign up to set email alerts
|

Tooth movement rate and anchorage lost during canine retraction: A maxillary and mandibular comparison

Abstract: Objectives: To investigate the canine retraction rate and anchorage loss during canine retraction using self-ligating (SL) brackets and conventional (CV) brackets. Differences between maxillary and mandibular rates were computed. Materials and Methods: Twenty-five subjects requiring four first premolar extractions were enrolled in this split-mouth, randomized clinical trial. Each patient had one upper canine and one lower can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
(65 reference statements)
1
6
0
Order By: Relevance
“…In general, the rate of tooth movement in the upper was slightly higher, but with a statistically non-significant difference. Our results agreed with Aslan et al (39) but were contradictory to Monini et al (41) who showed a higher maxillary rate of canine retraction.…”
Section: Table (2) Comparison Between the Four Studied Groups Accordi...supporting
confidence: 85%
“…In general, the rate of tooth movement in the upper was slightly higher, but with a statistically non-significant difference. Our results agreed with Aslan et al (39) but were contradictory to Monini et al (41) who showed a higher maxillary rate of canine retraction.…”
Section: Table (2) Comparison Between the Four Studied Groups Accordi...supporting
confidence: 85%
“…6 This also does not agree with a similar study by Monini et al in 2019 where canine retraction was done using conventional anchorage and the maxillary canines showed a greater rate of tooth movement than the mandibular canines. 7 The difference in retraction rate in high angle and low angle cases is statistically insignificant as per the paired ttest done in comparison between TADs in high and low angle cases.…”
Section: Retractionmentioning
confidence: 86%
“…Monini et al . [ 36 37 ] employed a vertical reference line perpendicular to the occlusal plane on both sides of oblique lateral cephalometric radiographs. The canine movement was indicated by the horizontal distance between the vertical reference line and the canine cusp point.…”
Section: Methods Of Measuring Distal Canine Movementmentioning
confidence: 99%